Influência da pressão hidrostática em Saccharomyces cerevisiae: correlação com estresses químicos e físicos - Soares, Fernando Lucas Palhano (2005)
Yeasts are unicellular organisms that are exposed to a highly variable environment,concerning the availability of nutrients, temperature, pH, radiation, access to oxygen and,specially, water activity. Evolution has selected yeasts to tolerate, to a certain extent, theseenvironmental stresses. High hydrostatic pressure (HHP) exerts a broad effect upon yeastcells, interfering with the cell membranes, cellular architecture and in processes ofpolymerisation and denaturation of proteins. Gene expression patterns in response to HHPrevealed a stress response profile. The majority of the upregulated genes are involved in stressdefence and carbohydrate metabolism while most of the repressed ones are in cell cycleprogression and protein synthesis categories (Fernandes et al, 2004). Nitric oxide (NO) is asimple and unique molecule that has diverse functions in organisms, including intracellularand intercellular messenger. The influence of NO on cell growth of Saccharomyces cerevisiaeand as a signal molecule in stress response of HHP was evaluated. Respiring cells were moresensitive to an increase in intracellular NO concentration than fermentatively growing cells.Low levels of NO demonstrated a cytoprotective effect during stress from HHP. Induction ofNO synthase was isoform-specific and dependent on the metabolic state of the cells and thestress response pathway. These results support the hypothesis that an increase in intracellularNO concentration leads to stress protection against HHP. In addition, the acquisition oftolerance to high hydrostatic pressure of 220 MPa (HHP) in response to a 0.4 mM hydrogenperoxide, 6 % ethanol or 10 ºC cold shock pretreatment for different lengths of times wasstudied in the yeast S. cerevisiae. The protection conferred by these different treatments wassimilar, around 3 log cycles and time-dependent. Analysis of the induction of the mostpressure up-regulated genes under these conditions was investigated by RT-PCR. Our resultsrevealed that the cell stress response to HHP shares common features with hydrogen peroxideand ethanol stresses, but differs in some way to cold shock. Also, it was seen that mildpressure induced cell cycle arrest and protection against severe stresses, such as hightemperature, high pressure and ultra cold shock. Nevertheless, this protection was only significant if the cells were incubated at atmospheric pressure after the HHP treatment.Expression of genes that were upregulated by HHP and are related to resistance to thisstresses were also analysed, and, for the majority of them, higher induction was attained after15 min post-pressurization. Taken together, the results imply an interconnection amongstresses.